Efektivitas Penguatan Komite Pembelajaran untuk Meningkatkan Pemahaman Kurikulum Merdeka pada Sekolah Penggerak Angkatan 3 Kota Semarang - Kurniati, Lenny; Kusumawati, Ratih (Manalisih: Jurnal Penelitian, Sosial, dan Humaniora; Vol 1 No 1 (2023): Manalisih: Jurnal Penelitian, Sosial, dan Humaniora, 2023)
The purpose of this study is to determine the effectiveness of the implementation of the Learning Committee Strengthening Training in the Driving School Program to increase understanding of the independent curriculum in a comprehensive manner. The study was conducted to the Mobilization School of 3 Middle School level in Semarang City with a research subject of 20 members of the Learning Committee from 5 State and Private Middle Schools consisting of Principals, School Supervisors, Subject Teachers, and BK Teachers. The method used in this study is quantitative descriptive where the data is obtained from the pretest and post test results and is statistically tested using the two -pace sample t test. The results show a significance value of 0,000 less than 0.05, which means it is true that there is a difference in the average understanding related to the independent curriculum before and after the implementation of the strengthening of the learning committee. The difference in average value is clarified with a description of the average pretest score of 69.42 which increased to 81.89 on the post test score. The conclusion of this study is that the strengthening of the Learning Committee has been proven to be effective in increasing the understanding of the independent curriculum. Therefore it would be very good if the training for strengthening the learning committee is not only limited to the school implementing school program, but more broadly for all schools that carry out the implementation of the independent curriculum.